Cartography Revealed - Borna Fuerst-Bjeliš (Continentes, 2014)
Borderlands are typical spaces where a multiplicity imperial and thus cultural, religious and ethnic contacts produces a multiplicity of perceptions and images. Through a number of examples of the Croatian borderlands, the main aim is to reveal the symbolic layer of the map that leads us into the process of imagining the past and constructing regional identities in the multicultural realities.